2004
DOI: 10.1002/mc.20066
|View full text |Cite
|
Sign up to set email alerts
|

Atypical protein kinase C‐ζ modulates clonogenicity, motility, and secretion of proteolytic enzymes in murine mammary cells

Abstract: In this paper, we investigated whether protein kinase C-zeta (PKC zeta), a member of the atypical PKC family, induces phenotypic alterations associated with malignant transformation and tumor progression in mammary cells. The stable overexpression of PKC zeta in immortalized mammary epithelial cells (NMuMG), activates the mitogenic extracellular signal-regulated kinase (ERK) pathway, enhanced clonal cell growth and exerts profound effects on proteases secretion. The effect on proteases expression seems to be s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 53 publications
1
28
1
Order By: Relevance
“…Furthermore, the expression of proteases has been associated with poor prognosis of breast cancer patients [51,52]. It has been reported in various cellular models that overexpression of different PKCs augments the secretion of both uPA and MMPs [36,53,54]. However, our studies show that overexpression of the classical PKCb1 reduces the secretion of uPA and MMP-2 in LM3 mammary tumor cells.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…Furthermore, the expression of proteases has been associated with poor prognosis of breast cancer patients [51,52]. It has been reported in various cellular models that overexpression of different PKCs augments the secretion of both uPA and MMPs [36,53,54]. However, our studies show that overexpression of the classical PKCb1 reduces the secretion of uPA and MMP-2 in LM3 mammary tumor cells.…”
Section: Discussioncontrasting
confidence: 53%
“…Forty-eight hours after transfection, cells were selected using 500 lg/ml G418. After selection, resistant clones were pooled to avoid clonal variations [36].…”
Section: Cell Line and Culture Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…We recently showed that the atypical PKC isoform PKCζ is a signaling intermediate for melanocyte dendrite formation [21]. PKCζ regulates mitogenesis, cell polarity and migration in other cell types and a recent study showed that PKCζ activation stimulates filopodia formation in motile cells [22][23][24][25]. Because of the importance of filopodia for melanosome transport and transfer in human melanocytes, PKCζ activation is likely to increase both dendricity and melanosome transfer to keratinocytes [26].…”
Section: Introductionmentioning
confidence: 99%
“…Altered PKC expression is observed in many tumors, and there is a large body of evidence linking PKC to invasion involving MMPs including MMP-9 (21,22). PKC activity, in particular that of nPKC, is of great interest with regard to T cell activation and consequently inflammatory diseases such as asthma, inflammatory bowel disease, and multiple sclerosis (23).…”
mentioning
confidence: 99%